Нина и заклятье Пернатого Змея: роман / М. Витчер ; перевод с итальянского В. Николаев - Витчер Муни (Махаон, 2007)
Экземпляры: б/ф-8 (20120702) / Инвентарный номер: 32962 / Цена: 50.00 / Авт.знак: В 54 / ББК: 84(4Ита)